The Effect of Integrative Learning on Improving Understanding of Science Concepts of Grade V Elementary Students Public School 40 Negeri Katon - Firdaus, Riyadh; Herpratiwi, Herpratiwi; Fitriawan, Helmy; Firdaus, Rangga (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
The problem in this study is the low learning outcomes of fifth grade students of SD Negeri 40 Negeri Katon Pesaaran. The purpose of this study was to determine the effect of integrative learning on increasing the understanding of science concepts of Class V Students of Elementary School Negeri 40 Negeri Katon. The research method used in this research is Quasi Experiment can be interpreted as research that is close to experiments or pseudo experiments. This research design uses a